Initiating VB‐Group Laminated NbS2 Electromagnetic Wave Absorber toward Superior Absorption Bandwidth as Large as 6.48 GHz through Phase Engineering Modulation. (27th October 2021) - Zhang, Huibin; Cheng, Junye; Wang, Honghan; Huang, Zehao; Zheng, Qingbin; Zheng, Guangping; Zhang, Deqing; Che, Renchao; Cao, Maosheng
Abstract: VB‐Group transition metal disulfides (TMDs) are considered excellent materials for electromagnetic wave (EMW) absorption because of their good conductivity and abundant active sites located at their edges and substrates, as compared with VIB‐Group TMDs. Herein, for the first time, EMW absorbers based on VB‐Group NbS2 nanosheets by using a facile one‐step solvothermal method are successfully prepared. The minimum reflection loss (RLmin ) can reach up to 43.85 dB with an effective absorption bandwidth of 6.48 GHz (11.52–18.00 GHz). The remarkable EMW absorption performance can also be reflected in the tunable frequency bands (C‐, X‐, and Ku‐bands), which is achieved by adjusting the contents of materials. Furthermore, the influence of the content of 2H‐phase and 1T‐phase in NbS2 on the EMW absorption performance is systematically investigated. The hierarchical hollow‐sphere structure of NbS2 promotes dielectric loss and the multiple reflection and absorption of EMW, and enhances the impedance matching and synergistic attenuation ability. This work demonstrates that the bottleneck of effective absorbing frequency band of single‐component dielectric EMW absorbing materials could be broken through, and paves a novel path towards developing broadband absorbing materials in EMW absorption. Abstract : For the first time, EMW absorbers based on VB‐group NbS2 nanosheets achieved via a one‐step solvothermal method are successfully prepared. The remarkable EMW absorption performance can also be reflected in the tunable frequency bands (C‐, X‐, and Ku‐bands). It opens up a new way for the development of broadband absorbing materials for electromagnetic wave absorption.